Исследование свойств молибдата циркония, образующегося при растворении ОЯТ - Леонова Л. А. Лилия Александровна; Карелин В. А. Владимир Александрович; Распутин И. В.; Никитин И. В. Иван Владимирович (2022, 2022)
Заглавие с экрана